High-Resolution Mapping of Crossover and Non-crossover Recombination Events by Whole-Genome Re-sequencing of an Avian Pedigree. - Linnéa Smeds; Carina F Mugal; Anna Qvarnström; Hans Ellegren (PLoS Genetics)
Recombination is an engine of genetic diversity and therefore constitutes a key process in evolutionary biology and genetics. While the outcome of crossover recombination can readily be detected as shuffled alleles by following the inheritance of markers in pedigreed families, the more precise location of both crossover and non-crossover recombination events has been difficult to pinpoint. As a consequence, we lack a detailed portrait of the recombination landscape for most organisms and knowledge on how this landscape impacts on sequence evolution at a local scale. To localize recombination events with high resolution in an avian system, we performed whole-genome re-sequencing at high coverage of a complete three-generation collared flycatcher pedigree. We identified 325 crossovers at a median resolution of 1.4 kb, with 86% of the events localized to <10 kb intervals. Observed crossover rates were in excellent agreement with data from linkage mapping, were 52% higher in male (3.56 cM/Mb) than in female meiosis (2.28 cM/Mb), and increased towards chromosome ends in male but not female meiosis. Crossover events were non-randomly distributed in the genome with several distinct hot-spots and a concentration to genic regions, with the highest density in promoters and CpG islands. We further identified 267 non-crossovers, whose location was significantly associated with crossover locations. We detected a significant transmission bias (0.18) in favour of 'strong' (G, C) over 'weak' (A, T) alleles at non-crossover events, providing direct evidence for the process of GC-biased gene conversion in an avian system. The approach taken in this study should be applicable to any species and would thereby help to provide a more comprehensive portray of the recombination landscape across organism groups.